Immediate effects of an anchor system on the stability limit of individuals with chronic dizziness of peripheral vestibular origin - Coelho,Almir Resende (2017)
Abstract Introduction The symptoms associated with chronic peripheral vestibulopathy exert a negative impact on the independence and quality of life of these individuals, and many individuals continue to suffer from these symptoms even after conventional vestibular rehabilitation. Objective To evaluate the acute effect of an anchor system for balance evaluation of patients with chronic dizziness who failed to respond to traditional vestibular rehabilitation. Methods Subjects over 50 years of age, presenting with chronic dizziness and postural instability of peripheral vestibular origin, participated in the study. The limit of stability was evaluated in three positions using the Balance Master® system: Position 1, standing with the arms along the body; Position 2, standing with the elbows bent at 90º (simulating holding the anchors); and Position 3, with the elbows bent at 90º holding the anchors. The variables of movement latency, endpoint excursion and directional control of movement were evaluated. Results Using the anchor system, significant reduction of time in the response at the beginning of the movement compared to Position 1 (p < 0.05); increased endpoint excursion in the left lateral direction compared to Position 1 (p < 0.05); and more directional control of movement in the anterior and posterior directions (p < 0.05) compared to the other positions, were found. Conclusion While using the system anchor, individuals with chronic peripheral vestibulopathy showed an immediate improvement in the stability limit in relation to the movement latency, endpoint excursion, and directional control of movement variables, suggesting that the haptic information aids postural control.